The Euro Zone Peripheral Countries’ Sovereign Debt Crisis: Also a Case of Non-Mature Democracies? - Costa Fernandes, Abel L.; Mota, Paulo R. (Panoeconomicus, 2013)
The euro zone peripheral countries face a profound sovereign debt crisis threatening the very existence of the euro as we know it. Therefore, the study of the various factors contributing to this crisis is of the utmost importance. Given the set of the twelve initial member States, the euro zone peripheral countries (Portugal, Greece, and Spain) have in common the fact that they are recent democracies. Independently from other valid approaches to this question, the specific contribution of this paper is to focus on the role played by institutional and political variables in the behavior of fiscal variables. We show that the behavior of these variables is indeed statistically different from the one observed for the other euro zone countries, which are mature democracies. These outcomes are also in line with what that literature expects from the relationship between non-mature democracies and the incidence of election year budget cycles. Key words: Fiscal policy, Political budget cycles, New democracies. JEL: H2, H5, H6.